Prioritizing the Factors Which Affect the Selection of Hotels by Consumers Traveling for Vacation with Analytical Hierarchy Process (AHP) Method - Göral, Ramazan (Journal of Tourism Management Research, 2020)
Selection of the best hotel for vacations requires a highly complex decision-making process. This complexity stems from factors including, but not limited to, the products of the hotel, information regarding the hotel and personal preferences. Determining the factors which affect the selection of the hotel by consumers traveling for vacations can improve their satisfaction by providing better quality services. The main purpose of this study is to define the factors which affect the selection of hotels by consumers traveling for vacation and to prioritize these factors from the customers’ viewpoint. Another purpose of this study is to analyze whether these factors vary by gender. In this context, a comprehensive literature research has been done in order to define the factors for selection of hotels. The method of analysis for carried out for this study is the Analytical Hierarchy Process (AHP) method, and the data for analysis has been gathered by survey method. The survey has been conducted on a panel of instructors employed at S.U. Beyşehir Ali Akkanat Campus who travel for vacation at least once a year. Research findings show that prioritizing the factors which affect the selection of hotels can vary by gender. However, putting the role of gender aside, factors which affect consumers the most for their travels for vacation are Safety and Security, Pleasure, Room Facilities; whereas factors which affect the consumers the least are Informing, Parking Lots and Network Services.